Anticancer evaluation of new organometallic ruthenium(ii) flavone complexes. Issue 2 (15th December 2022) - Khater, Mai; Brazier, John A.; Greco, Francesca; Osborn, Helen M. I.
Abstract : Targeting multiple malignancy features such as angiogenesis, proliferation and metastasis with one molecule is an effective strategy in developing potent anticancer agents. Abstract : Targeting multiple malignancy features such as angiogenesis, proliferation and metastasis with one molecule is an effective strategy in developing potent anticancer agents. Ruthenium metal complexation to bioactive scaffolds is reported to enhance their biological activities. Herein, we evaluate the impact of Ru chelation on the pharmacological activities of two bioactive flavones (1 and 2 ) as anticancer candidates. The novel Ru complexes (1Ru and 2Ru ) caused a loss of their parent molecules' antiangiogenic activities in an endothelial cell tube formation assay. 1Ru enhanced the antiproliferative and antimigratory activities of its 4-oxoflavone 1 on MCF-7 breast cancer cells (IC50 = 66.15 ± 5 μM and 50% migration inhibition, p < 0.01 at 1 μM). 2Ru diminished 4-thioflavone's (2 ) cytotoxic activity on MCF-7 and MDA-MB-231 yet significantly enhanced 2 's migration inhibition ( p < 0.05) particularly on the MDA-MB-231 cell line. The test derivatives also showed non-intercalative interaction with VEGF and c-myc i-motif DNA sequences.